Claudin expression during early postnatal development of the murine cochlea - Kudo, Takayuki; Wangemann, Philine; Marcus, Daniel C. (My University, 2018)
Background: Claudins are major components of tight junctions, which form the paracellular barrier between the cochlear luminal and abluminal fluid compartments that supports the large transepithelial voltage difference and the large concentration differences of K+, Na+ and Ca2+ needed for normal cochlear function. Claudins are a family of more than 20 subtypes, but our knowledge about expression and localization of each subtype in the cochlea is limited. Results: We examined by quantitative RT-PCR the expression of the mRNA of 24 claudin isoforms in mouse cochlea during postnatal development and localized the expression in separated fractions of the cochlea. Transcripts of 21 claudin isoforms were detected at all ages, while 3 isoforms (Cldn-16, ??17 and ??18) were not detected. Claudins that increased expression during development include Cldn-9, ??13, ??14, ??15, and -19v2, while Cldn-6 decreased. Those that do not change expression level during postnatal development include Cldn-1, ??2, ??3, ??4, ??5, ??7, ??8, ?10v1, ?10v2, ??11, ??12, ?19v1, ??20, ??22, and???23. Our investigation revealed unique localization of some claudins. In particular, Cldn-13 expression rapidly increases during early development and is mainly expressed in bone but only minimally in the lateral wall (including stria vascularis) and in the medial region (including the organ of Corti). No statistically significant changes in expression of Cldn-11, ??13, or ??14 were found in the cochlea of Slc26a4 ?/? mice compared to Slc26a4 +/? mice. Conclusions: We demonstrated developmental patterns of claudin isoform transcript expression in the murine cochlea. Most of the claudins were associated with stria vascularis and organ of Corti, tissue fractions rich in tight junctions. However, this study suggests a novel function of Cldn-13 in the cochlea, which may be linked to cochlear bone marrow maturation.
Citation: Kudo, T., Wangemann, P., & Marcus, D. C. (2018). Claudin expression during early postnatal development of the murine cochlea. BMC Physiology, 18(1), 1. https://doi.org/10.1186/s12899-018-0035-1
Keywords: Tight junctions; Inner ear; Pendrin; SLC26A4; Mouse